(untitled) (Architecture Image Studies, 2024)
This paper deals with the architecture of the national and university library of Kosovo. internal and external image. artistic pages, domes, facade, outer space, contact with this space. The rest of the paper focuses on the exhibition of dictators like Kim Jung, whose photo was exhibited next to the Albanian renaissance. Their photographs were exhibited in the space of this Library. These materials from Korea elicited strong reactions from critics, who mainly saw the exhibition as promotion of a dictatorial system and its leaders. It was noted that this exhibition was held next to the portraits of Albanian National Renaissance figures, who were long-standing residents of the Library hall. On the second floor there were photographs, brochures and other stuff that presented North Korean life. Above all, there were two large photos of two former North Korean dictators: Kim Jong Sung and Kim Jong IL. Ah, and let’s not forget Ismail Kadare’s quote: “The relations of a great writer with a dictator are complex and difficult to explain, because they are both tyrants, but in this confrontation, the dictator is a false tyrant…”